Needs Analysis for Incorporating Translanguaging in EMI/ELT Classrooms Exploring Multiculturalism in NEP 2020 - Dalal, Garima (JOURNAL OF INDIAN EDUCATION, 2024)
This paper investigates ‘Translanguaging’ in English as a Medium of Instruction (EMI) and English Language Teaching (ELT) classrooms. With the National Education Policy (NEP) 2020, this study reflects on translanguaging and investigates its implications for multilingual education. A needs analysis involving 177 participants from central universities in North India assesses student attitudes, preferences, and challenges related to translanguaging. The findings reveal positive student reception, emphasising benefits in comprehension, inclusivity and cultural exchange. Despite challenges, respondents express a favourable stance, advocating for selective translanguaging. The study contributes to ongoing discussions on inclusive language pedagogies, cultural awareness and transformative approaches aligned with NEP-2020 goals. It highlights the potential of translanguaging to reshape language education paradigms, fostering a more inclusive, multilingual learning environment.